Climate Change and an Agronomic Journey from the Past to the Present for the Future: A Past Reference Investigation and Current Experiment (PRICE) Study - Hyunkyeong Min; Hyeon-Seok Lee; Chun-Kuen Lee; Woo-Jung Choi; Bo-Keun Ha; Hyeongju Lee; Seo-Ho Shin; Kyu-Nam An; Dong-Kwan Kim; Oh-Do Kwon; Jonghan Ko; Jaeil Cho; et al. (Agronomy, 2023)
According to numerous chamber and free-air CO2 enrichment (FACE) studies with artificially raised CO2 concentration and/or temperature, it appears that increasing atmospheric CO2 concentrations ([CO2]) stimulates crop yield. However, there is still controversy about the extent of the yield stimulation by elevating [CO2] and concern regarding the potential adverse effects when temperature rises concomitantly. Here, we tested the effects of natural elevated [CO2] (ca. 120 ppm above the ambient level in 100 years ago) and warming (ca. 1.7–3.2 °C above the ambient level 100 years ago) on rice growth and yield over three crop seasons via a past reference investigation and current experiment (PRICE) study. In 2020–2022, the rice cultivar Tamanishiki (Oryza sativa, ssp. japonica) was grown in Wagner’s pots (1/2000 a) at the experiment fields of Chonnam National University (35°10′ N, 126°53′ E), Gwangju, Korea, according to the pot trial methodology of the reference experiment conducted in 1920–1922. Elevated [CO2] and temperature over the last 100 years significantly stimulated plant height (13.4% on average), tiller number (11.5%), and shoot biomass (10.8%). In addition, elevated [CO2] and warming resulted in a marked acceleration of flowering phenology (6.8% or 5.1 days), potentially leading to adverse effects on tiller number and grain yield. While the harvest index exhibited a dramatic reduction (12.2%), grain yield remained unchanged with elevated [CO2] and warming over the last century. The response of these crop parameters to elevated [CO2] and warming was highly sensitive to sunshine duration during the period from transplanting to heading. Despite the pot-based observations, considering a piecewise response pattern of C3 crop productivity to [CO2] of <500 ppm, our observations demonstrate realistic responses of rice crops to elevated [CO2] (+120 ppm) and moderate warming (+1.7–3.2 °C) in the absence of adaptation measures (e.g., cultivars and agronomic management practices). Hence, our results suggest that the PRICE platform may provide a promising way to better understand and forecast the net impact of climate change on major crops that have historical and experimental archived data, like rice, wheat, and soybean.